Antimicrobial activity of some ethnomedicinal plants used by Paliyar tribe from Tamil Nadu, India - Ayyanar Muniappan; Duraipandiyan Veeramuthu; Ignacimuthu Savarimuthu (BMC, 2006)
Abstract Background Antimicrobial activity of 18 ethnomedicinal plant extracts were evaluated against nine bacterial strains (Bacillus subtilis, Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Escherichia coli, Klebsiella pneumonia, Pseudomonas aeruginosa, Ervinia sp, Proteus vulgaris) and one fungal strain (Candida albicans). The collected ethnomedicinal plants were used in folk medicine in the treatment of skin diseases, venereal diseases, respiratory problems and nervous disorders. Methods Plants were collected from Palni hills of Southern Western Ghats and the ethnobotanical data were gathered from traditional healers who inhabit the study area. The hexane and methanol extracts were obtained by cold percolation method and the antimicrobial activity was found using paper disc diffusion method. All microorganisms were obtained from Christian Medical College, Vellore, Tamil Nadu, India. Results The results indicated that out of 18 plants, 10 plants exhibited antimicrobial activity against one or more of the tested microorganisms at three different concentrations of 1.25, 2.5 and 5 mg/disc. Among the plants tested, Acalypha fruticosa, Peltophorum pterocarpum, Toddalia asiatica,Cassia auriculata, Punica granatum and Syzygium lineare were most active. The highest antifungal activity was exhibited by methanol extract of Peltophorum pterocarpum and Punica granatum against Candida albicans. Conclusion This study evaluated the antimicrobial activity of the some ethnomedicinal plants used in folkloric medicine. Compared to hexane extract, methanol extract showed significant activity against tested organisms. This study also showed that Toddalia asiatica, Syzygium lineare, Acalypha fruticosa and Peltophorum pterocarpum could be potential sources of new antimicrobial agents.